If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.8(m + -5) + 2 = 10 Reorder the terms: 0.8(-5 + m) + 2 = 10 (-5 * 0.8 + m * 0.8) + 2 = 10 (-4 + 0.8m) + 2 = 10 Reorder the terms: -4 + 2 + 0.8m = 10 Combine like terms: -4 + 2 = -2 -2 + 0.8m = 10 Solving -2 + 0.8m = 10 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 0.8m = 10 + 2 Combine like terms: -2 + 2 = 0 0 + 0.8m = 10 + 2 0.8m = 10 + 2 Combine like terms: 10 + 2 = 12 0.8m = 12 Divide each side by '0.8'. m = 15 Simplifying m = 15
| 2x-2(7x-11)=-26 | | 35r^2+6r-8= | | -52+5a=-127 | | (5x)+(3x+20)+(4x+5)+(5x-5)=360 | | 8[-2(6-8)+14]= | | 6x^2-3=2+4x | | a=.96-145 | | 10+y=5x+x^2 | | 4x+9=2x+16 | | -9(x+5)+7=-12 | | 3x+2+H=10x+12 | | h-1.4=5 | | h-14=5 | | n+(-10)=5 | | r^2+1=-14 | | -16+z=7 | | (5x-5)+(6x-2)+(7x+7)=180 | | (3x^2-5x+6)+(9-8x-4x^2)= | | V+(3v-15)+(v+11)+18=229 | | 7x+8=44 | | (3x^2-3x+5)+(-x^2+x-6)= | | 7(7+x)=7 | | 3(5x+9)+4=-14 | | 8*-4= | | 3(y+1)=20 | | 2+4x=x+8 | | 0=r^2-64 | | -2x+9+11x=108 | | X-2=0.6 | | 0=r^2-1218.01 | | -2x^2-8x+24=0 | | -5x+40=1-2x |